Contribution of Resin Commodity Exports to Gross Domestic Product and Employment in Indonesia - Ferry Noldy Langelo; Heru Subiantoro; Pudji Astuti (PT Publikasiku Academic Solution, 2024)
Exports of resin commodities significantly affect Indonesia's economy, particularly in terms of Gross Domestic Product (GDP) and employment. This study aims to analyzethe effects of resin commodity exports on Indonesia's GDP and employment opportunities, and to provide recommendations for enhancing the sector's contribution through strategic initiatives. The research employs the Error Correction Model (ECM) to assess the relationship between resin exports, GDP, and employment, utilizing secondary data over the past decade. Results indicate a strong positive correlation between resin exports and GDP growth, with the latter significantly influenced by export revenue. The findings also reveal that the resin sector creates numerous job opportunities, benefiting not only the industry itself but also related sectors such as logistics and manufacturing. Enhanced export capabilities can lead to increased national income and reduced trade imbalances, further stabilizing the economy. In conclusion, the study highlights the importance of resin commodity exports in driving economic growth in Indonesia. It provides actionable insights for policymakers to strengthen the resin sector, improve product quality, and expand market access. By focusing on sustainable practices and technological advancements, Indonesia can capitalize on its natural resource wealth, fostering job creation and elevating living standards across local communities.